Textured Organogel Films Showing Unusual Thermoresponsive Dewetting, Icephobic, and Optical Properties. Issue 2 (22nd November 2018) - Urata, Chihiro; Hönes, Roland; Sato, Tomoya; Kakiuchida, Hiroshi; Matsuo, Yasutaka; Hozumi, Atsushi
Abstract: Textured organogel films showing thermoresponsive (TR)‐syneretic and optical behaviors are fabricated based on soft lithography, using micro/nanostructured master moulds, of polydimethylsiloxane infused with polymethylphenylsiloxane (PMPS) as a lubricating oil. The critical syneretic temperature (CST) of the organogels can be arbitrarily tuned in the range of −15–50 °C by varying the volume of PMPS. Below the CST, the oil is spontaneously released from the inside of the gel matrices to the topmost surface, and vice versa, and it gradually returns back to the matrices above the CST. In the lubricated state, the textured TR‐organogel film surfaces exhibit excellent dynamic hydrophobicity and icephobicity, i.e., ice can be easily removed from the surface without any additional force. Simultaneously, optical properties derived from surface micro/nanotextures, such as diffraction and antireflection, respectively, are clearly observed above the CST and disappear below the CST, because the surface textures are buried by the released PMPS. These unusual TR‐surface functionalities are found to be repeatable/switchable for several tens of times. Abstract : Slippery organogel films possessing thermoresponsive and repeatable/reversible liquid releasing (syneresis) and absorbing (reverse‐syneresis) properties are prepared from a simple cross‐linking reaction of polydimethylsiloxane under the presence of an infusing oil. By introducing micro/nanostructures using soft lithography, the textured organogel films attain unusual thermoresponsive dewetting, icephobic, and optical diffraction/antireflection properties.